1970
DOI: 10.3126/kumj.v7i2.2706
|View full text |Cite
|
Sign up to set email alerts
|

Hospital based analytic study of peptic ulcer disease in patients with dyspeptic symptoms

Abstract: Background: Peptic ulcer disease is one of the most common diseases prevalent in developing country like Nepal and with availability of endoscopy there have been increase in diagnosis and therapeutic use of endoscopy. Objective: The aim of this study is to investigate the prevalence of peptic ulcer disease in patient who came for upper gastrointestinal endoscopy in Kathmandu Medical College Teaching Hospital. Materials and methods:All patients who were referred to department of endoscopy from outpatient depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Another fascinating result is the 2.1-fold higher prevalence of strains with lowvirulence cagA ? /cagE -genotype in women compared with in men, which may imply a higher frequency of more virulent H. pylori strains in men and can explain, at least partially, the greater frequency and severity of gastroduodenal diseases such as duodenal ulcer in men than in women, as reported in some studies (Jafarzadeh et al 2007;Sharma et al 2009;Feinstein et al 2010).…”
Section: Discussionmentioning
confidence: 85%
“…Another fascinating result is the 2.1-fold higher prevalence of strains with lowvirulence cagA ? /cagE -genotype in women compared with in men, which may imply a higher frequency of more virulent H. pylori strains in men and can explain, at least partially, the greater frequency and severity of gastroduodenal diseases such as duodenal ulcer in men than in women, as reported in some studies (Jafarzadeh et al 2007;Sharma et al 2009;Feinstein et al 2010).…”
Section: Discussionmentioning
confidence: 85%
“…[10] Our study revealed that among the diagnosed medical conditions, the most prevalent was gastritis in 36% of the sample population; gastritis is a quite common health problem for the people of Nepal. [44] A study of 319 dyspeptic patients in Nepal Medical College (NMC) Teaching Hospital, Kathmandu, Bagmati Zone, Nepal revealed that the most common endoscopic finding in these patients was gastritis as found in 47.6% of the patients followed by normal findings in 17.8%. [45] In a Chinese study involving 25,627 random subjects aged 40 years or more, the overall prevalence of COPD was 8.2% (men: 12.4%; women: 5.1%).…”
Section: Discussionmentioning
confidence: 99%
“…3 In the United States, approximately four million people have duodenal and gastric ulcer while 180,000 patients are hospitalized each year due to peptic ulcer disease. There is 10% likelihood of developing peptic ulcer in about 10% males and 4% females.…”
Section: Introductionmentioning
confidence: 99%
“…There is 10% likelihood of developing peptic ulcer in about 10% males and 4% females. 1,3 Peptic ulcer incidence in India is 2.9% and for gastric ulcer is 2.7%. important process of the stomach.…”
Section: Introductionmentioning
confidence: 99%